2020
DOI: 10.1111/dme.14316
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the management of diabetes services and patients during the COVID‐19 pandemic

Abstract: The UK National Diabetes Inpatient COVID Response Group was formed at the end of March 2020 to support the provision of diabetes inpatient care during the COVID pandemic. It was formed in response to two emerging needs. First to ensure that basic diabetes services are secured and maintained at a time when there was a call for re-deployment to support the need for general medical expertise across secondary care services. The second was to provide simple safe diabetes guidelines for use by specialists and non-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 2 publications
0
69
0
Order By: Relevance
“…Giver the former use, it is not surprising that metformin has been considered among the drugs which could be repurposed against COVID-19, with potential antiviral effects through activation of the AMP-activated protein kinase (AMPK) pathway that would cause changes in the ACE-2 receptor and block the entry of SARS-CoV-2 into host cells [68]. However, metformin use can promote lactic acidosis in the context of marked dehydration and renal impairment in severe COVID-19; hence, women with PCOS under metformin treatment is advisable to consider stopping this agent when symptomatic with COVID-19, particularly if they become unstable, as also recommended for patients with diabetes [69][70][71].…”
Section: Metformin Treatmentmentioning
confidence: 99%
“…Giver the former use, it is not surprising that metformin has been considered among the drugs which could be repurposed against COVID-19, with potential antiviral effects through activation of the AMP-activated protein kinase (AMPK) pathway that would cause changes in the ACE-2 receptor and block the entry of SARS-CoV-2 into host cells [68]. However, metformin use can promote lactic acidosis in the context of marked dehydration and renal impairment in severe COVID-19; hence, women with PCOS under metformin treatment is advisable to consider stopping this agent when symptomatic with COVID-19, particularly if they become unstable, as also recommended for patients with diabetes [69][70][71].…”
Section: Metformin Treatmentmentioning
confidence: 99%
“…The increased morbidity and mortality of COVID-19 patients was particularly seen in older and those presenting comorbidities conditions, commonly cardiovascular diseases and diabetes [21]. Emerging data suggested that individual with diabetes comorbidity were at high risk for COVID-19 infection, and increased risk for complications including death [22,23]. To date,…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk of euglycemic DKA occurs due to a reduced appetite leading to decreased carbohydrate consumption along with dehydration due to high fever or vomiting/diarrhoea and the osmotic diuretic effect of COVID-19 infection. 11 In addition, drug interactions are major concerns while prescribing SGLT2i. In view of these complications, health agencies had warned about safety concerns for SLGT2i and the risk of DKA in patients with both diabetes and COVID-19 infection.…”
Section: Challenges In Use Of Sglt-2i In Covid-19mentioning
confidence: 99%
“…In this setting, they have recommended to avoid SGLT2 inhibitors in all patients with risk factors for developing symptoms or serious complications of COVID-19. 11 The potential role of SGLT-2i is being explored in the form of Dapagliflozin in Respiratory Failure in Patients with COVID-19 (DARE-19, NCT04350593) trial 12 which is a phase III multinational RCT. This trial includes patients with mild-moderate COVID-19 infection and at least one of the following: type 2 diabetes, hypertension, atherosclerotic cardiovascular disease, heart failure and stage 3-4 chronic kidney disease who shall be randomised to receive either dapagliflozin 10 mg once daily or placebo along with standard of care.…”
Section: Challenges In Use Of Sglt-2i In Covid-19mentioning
confidence: 99%